Epidemiological studies of parvovirus infections in calves on endemically infected properties - Durham, P.J.K. (Res Vet Sci, 1985)
Bovine parvovirus serology and virus excretion were monitored in calves located on three endemically infected North Queensland properties. Maternally derived serum antibody to bovine parvovirus was found to have a half-life of 19 days. On all three properties, calves developed intestinal bovine parvovirus infection with seroconversion soon after weaning. This occurred more promptly where the environment was subject to heavier bovine parvovirus contamination due to management practices. The concurrent presence of moderate levels of residual serum antibody had only minor influence on the onset of the infection. On one beef cattle property, onset of intestinal bovine parvovirus infection was associated with an outbreak of post-weaning diarrhoea. Anthelmintic treatment trials indicated that this syndrome was unrelated to helminth burdens, though coccidi-osis appeared responsible for occasional subsequent cases of dysentery. It was considered that bovine parvovirus may have significantly contributed to the development of the diarrhoea syndrome, in conjunction with substantial weaning stresses.